2019
DOI: 10.1002/jcop.22265
|View full text |Cite|
|
Sign up to set email alerts
|

Enforcement trends in the city of St. Louis from 2007 to 2017: Exploring variability in arrests and criminal summonses over time and across communities

Abstract: The goal of this study is twofold: (a) to describe trends in enforcement activity in the city of St. Louis from 2007 through 2017 and (b) to document community variation in these trends. Five types of enforcement actions are examined: felony, misdemeanor, municipal, and bench warrant arrests and criminal summonses-in-lieu of arrest. Results indicate that enforcement activity decreased over the study period, particularly for nonfelony arrests among Blacks. City-wide trends obscure some variability in neighborho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…From our data, we cannot estimate how often warrants for summons failures to appear lead to arrests in New York City. However, a recent study in St. Louis found that in 2017, ~1% of all residents were arrested for similar warrants (25). Of course, the proportion of defendants who are arrested for these warrants is necessarily higher than the proportion of residents, but if even 1% of defendants in our sample were arrested for failure to appear, then our interventions would have saved approximately $140,000 from August 2016 to September 2019.…”
Section: Discussionmentioning
confidence: 77%
“…From our data, we cannot estimate how often warrants for summons failures to appear lead to arrests in New York City. However, a recent study in St. Louis found that in 2017, ~1% of all residents were arrested for similar warrants (25). Of course, the proportion of defendants who are arrested for these warrants is necessarily higher than the proportion of residents, but if even 1% of defendants in our sample were arrested for failure to appear, then our interventions would have saved approximately $140,000 from August 2016 to September 2019.…”
Section: Discussionmentioning
confidence: 77%
“…Results by Glazener, Kozlowski, Lynch, and Smith () and Hughes, Campbell, and Schaefer () suggest that calls for service and crime, respectively, are strongly related to enforcement and that neighborhood racial composition is less tied to enforcement after accounting for these factors. In contrast, Slocum, Huebner, Greene, and Rosenfeld () found that neighborhoods with a higher proportion of Black residents had higher rates of enforcement (with the exception of municipal arrests) even after accounting for calls for service and other sociodemographic features of the community. They also found, within the context of citywide declines in lower level enforcement, the most dramatic declines were for communities with a greater proportion of Black residents.…”
Section: Community Characteristics and Enforcementmentioning
confidence: 96%
“…In addition, the papers found divergent relationships with economic disadvantage and enforcement actions. Glazener et al () and Slocum et al () found higher rates of enforcement for both lower level offenses and felonies among areas with greater economic disadvantage, while Hughes et al () only found a significant relationship with lower level citations and in the opposite direction. That is, communities with greater economic disadvantage had fewer lower level citations issued.…”
Section: Community Characteristics and Enforcementmentioning
confidence: 97%
See 1 more Smart Citation
“…In (Slocum, Huebner, Greene, & Rosenfeld, 2020), authors noticed that the race specific population counts used to compute the rates presented in Section 5.2 are incorrect. These population counts were not used in any other analyses, and the results in all other sections of the paper remain unchanged.…”
Section: Figurementioning
confidence: 99%